"Performance of sweetpotato marketing system in Umuahia market, Abia State, Nigeria. " (2011)
The study was carried out to evaluate the profitability of sweetpotato in the market among other objectives. One hundred wholesalers and one hundred retailers respectively were randomly selected in the market. Economic indices used to evaluate the marketing system included the marketing margin, marketing efficiency, return on investment, benefit cost ratio and the Gini coefficient. The results of the marketing margin were N6, 300.00 and N4,01O.00 respectively for wholesalers and retailers. Benefit cost ratio showed that an investor would gain N1.15 and Nl.08 respectively for every Nl.00 spent in marketing sweetpotato. The Gini coefficient showed inequality in income distribution thus signifying an imperfect competitive market. Government policies should be directed towards reducing transportation costs, rent charged by the Local Government Authority and provision of micro credit for the traders to expand their purchases.